ECM1 modified HF-MSCs targeting HSC attenuate liver cirrhosis by inhibiting the TGF-β/Smad signaling pathway - Qi Liu; Chengqian Lv; Qianqian Huang; Lei Zhao; Xiaoli Sun; Dandan Ning; Jingyang Liu; Yanan Jiang; Shizhu Jin (Cell Death Discovery, 2022)
Abstract Hair follicle-derived mesenchymal stem cells (HF-MSCs) show considerable therapeutic potential for liver cirrhosis (LC). To improve the effectiveness of naïve HF-MSC treatments on LC, we used bioinformatic tools to identify an exogenous gene targeting HSCs among the differentially expressed genes (DEGs) in LC to modify HF-MSCs. Extracellular matrix protein 1 (ECM1) was identified as a DEG that was significantly downregulated in the cirrhotic liver. Then, ECM1-overexpressing HF-MSCs (ECM1-HF-MSCs) were transplanted into mice with LC to explore the effectiveness and correlated mechanism of gene-overexpressing HF-MSCs on LC. The results showed that ECM1-HF-MSCs significantly improved liver function and liver pathological injury in LC after cell therapy relative to the other treatment groups. Moreover, we found that ECM1-HF-MSCs homed to the injured liver and expressed the hepatocyte-specific surface markers ALB, CK18, and AFP. In addition, hepatic stellate cell (HSC) activation was significantly inhibited in the cell treatment groups in vivo and in vitro, especially in the ECM1-HF-MSC group. Additionally, TGF-β/Smad signal inhibition was the most significant in the ECM1-HF-MSC group in vivo and in vitro. The findings indicate that the genetic modification of HF-MSCs with bioinformatic tools may provide a broad perspective for precision treatment of LC.